Determinants for Increased Efficiency of Sitio Busngol Farmers Association Highland Vegetable Production in Puerto Princesa City - Dicar, Ziedwrick A. (International Journal of Multidisciplinary: Applied Business and Education Research, 2024)
Highland vegetable farming is the cultivation of vegetables in high-altitude regions to take advantage of the unique climatic conditions found at higher elevations, such as cooler temperatures, greater rainfall, and more fertile soil. In 2020, a successful pilot production of highland vegetables in Puerto Princesa City was conducted by local government in partnership with the Sitio Busngol Farmers Association (SBFA). Recently, the farmers are able to produce significant amount of bell pepper, cabbage, cauliflower, broccoli, celery, lettuce, chines cabbage, onion leaves, and snap beans. A good indication that the location has a potential of producing an ample amount of the commodity to sustain the demand of the city and to decrease its dependency in Cordillera region. Thus, this study examined the determinants for increased efficiency of the farmers in producing highland vegetables by assessing their profile and farming practices in relation to the Good Agricultural Practices (GAP) for Fruits and Vegetable Farming – Code of Practice of the Philippines. Further, this study examined the relationship between their total harvest and farming practices. This study used descriptive correlational quantitative research design to attain the objectives and answer the research questions. A researcher-made questionnaire underwent content validation and reliability testing with an alpha coefficient of .917 (Excellent). Ten (10) member farmers of SBFA served as respondents of the study. Using Pearson Correlation Coefficient, there is a strong positive relationship between the Total Harvest of the farmers and their farming practices in terms of Source of Irrigation Water and Management, Post-Harvest Handling and Storage, and Transport and Marketing respectively as evidenced by their p-values.